2021
DOI: 10.3126/kumj.v19i3.49705
|View full text |Cite
|
Sign up to set email alerts
|

Histological Examination of Tissue Obtained in Early Pregnancy Loss

Abstract: Background It is a routine practice to send histological sample after surgical evacuation of early pregnancy loss. Objective This study was carried out to see the justification of regular histological study by carrying out the histological study of early pregnancy loss and to find the prevalence of gestational trophoblastic disease in early pregnancy loss. Method It was a descriptive prospective study, conducted in Nepal medical college teaching hospital from February to October 2020 in Obstetrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…A total of 57% of cases were observed in younger women, in agreement with findings from previous studies reporting that extremes of maternal ages (below 20 years or above 40 years) are associated with greater risk of molar pregnancy. 26 , 27 Nonetheless, we observed a higher incidence rate than that of another study in our country at sea level area, which has reported a rate of 0.09%. Although the incidence of gestational trophoblastic diseases has declined with the rapid socio-medical development of the KSA, this study indicated a higher percentage of molar pregnancies than those observed in other studies in high-altitude areas.…”
Section: Discussioncontrasting
confidence: 75%
“…A total of 57% of cases were observed in younger women, in agreement with findings from previous studies reporting that extremes of maternal ages (below 20 years or above 40 years) are associated with greater risk of molar pregnancy. 26 , 27 Nonetheless, we observed a higher incidence rate than that of another study in our country at sea level area, which has reported a rate of 0.09%. Although the incidence of gestational trophoblastic diseases has declined with the rapid socio-medical development of the KSA, this study indicated a higher percentage of molar pregnancies than those observed in other studies in high-altitude areas.…”
Section: Discussioncontrasting
confidence: 75%